Lower Limb Muscle Endurance and Its Relationship to Functional Mobility in the Elderly of Puskesmas II Tabanan - Mahendra, I Putu Wahyu; Luh Putu Ratna Sundari; Nur Basuki (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to determine the relationship between lower limb muscle endurance and functional mobility among elderly individuals at Puskesmas II Tabanan. This observational analytic study employed a cross-sectional design and included 63 elderly individuals aged 60–69 years with normal BMI based on Asian adult standards. Participants were selected through simple random sampling. Lower limb muscle endurance was assessed using the 30-Second Chair Stand Test (30s-CST), while functional mobility was measured using the Timed Up and Go Test (TUGT). Data were analyzed using the Spearman’s Rho correlation test due to non-normal distribution. The Spearman’s correlation test showed a strong and statistically significant negative correlation between lower limb muscle endurance and functional mobility (r = -0.535, p = 0.000). Participants with higher repetition counts in the 30s-CST completed the TUGT in shorter times, indicating better mobility performance. There is a significant inverse relationship between lower limb muscle endurance and functional mobility in older adults. Routine assessment and targeted interventions focusing on muscle endurance should be integrated into geriatric healthcare programs to enhance mobility and reduce fall risk.